Study Skills for Early Years Students - Mitchell Alison (Hodder & Stoughton, 2001)
This book covers the complete range of assessments that early years students must cover, including coursework, short answer exams, multiple choices oral presentations and building portfolios. The Most Effective Way to Learn, Finding the Right Environment, Becoming Less Stressed Finding Information, Storing and Retrieving Information, Writing Assignments, the Purpose of Assignments, Basic Writing Skills, Advantages of Word Processing Assignment, Preparing for Examinations, Giving an Oral Presentation or Taking Part in a Class Discussion, the Importance of Being Able to Give Good Presentations, Building a Portfolio, Top Ten Tips, Bibliography, Resources.